구조방정식모형을 통한 이상적 L2 자아, 노력, 성적 간의 관계 - 곽미순(Gwak Misoon), 박기표(Park Gipyo), 김용석(Kim Yongsuk) (영어교과교육, 2020)
This study aims to investigate the contribution of the ideal L2 self to academic performance with the mediation of intended efforts. The data were gathered among university students learning English in Korea, using the ideal L2 self-questionnaire. The results of exploratory factor analysis indicate that the ideal L2 self is comprised of eight factors: learning strategies, emotion, achievement will, integrative motivation, possibility, logical expression, instrumental motivation, and thought frequency. This result was confirmed by confirmatory factor analysis using various fit indices, including χ2/df, GFI, CFI, TLI, and RMSEA. The results of structural equation modeling (SEM) showed that the direct and total contributions of the ideal L2 self to academic performance mediated by efforts are statistically significant and that the contribution of efforts to academic performance is not. In terms of the components of the ideal L2 self, the mean scores of possibility, instrumental motivation, and integrative motivation in order of magnitude were relatively higher, whereas the lowest mean score was found in learning strategies. These findings are discussed on the basis of current research on L2 motivation and related subject areas. KCI Citation Count: 0